Normative Data and Determinants of Macular, Disc, and Peripapillary Vascular Density in Healthy Myopic Children Using Optical Coherence Tomography Angiography - Chen, Ruru; Lian, Hengli; McAlinden, Colm; Skiadaresi, Eirini; Liu, Siyu; Wan, Ting; Diao, Kai; Pan, Hongxian; Qu, Jia; Huang, Jinhai; Li, Yiyu (Frontiers in Medicine, 2022)
Objective: To establish a normative database for the vascular density (VD) in macular, disc and peripapillary regions in healthy myopic children and to evaluate associated ocular features with optical coherence tomography angiography (OCTA). Methods: This was an observational, prospective and cross-sectional study. 776 Chinese healthy myopic children (375 boys and 401 girls) were enrolled, mean (±SD) age 9.84 ± 1.98 (range 6-16) years. En-face angiogram OCTA was performed on 6×6mm retinal and 4.5×4.5mm disc regions. Vascular density (VD) measurements in the macular retina were segmented into the four regions: superficial capillary plexus (SCP), intermediate capillary plexus (ICP), deep capillary plexus (DCP), and choriocapillaris (CC). Correlations between macular, disc and peripapillary VD and possible influencing factors (age, gender, AL, SER, right/left eye, and signal strength index (SSI) were assessed by Pearson’s correlation and multivariate regression analysis. Results: For macular scans, the corrected VD in the ICP region was (48.25 ± 4.24) % for the whole macular retina. The macular ICP VD in most sections was lower than the SCP, DCP and CC (all P < 0.001). The corrected VD in CC was (72.96 ± 4.42) % for the whole macular retina. The macular CC VD in every section was all higher than the SCP, ICP and DCP (all P < 0.001). The size of foveal avascular zone (FAZ) and foveal VD 300 (FD-300) was 0.28 ± 0.10 mm2 and (58.43 ± 4.17) % respectively. For disc scans, the corrected VD was (58.04 ± 2.73) % for the whole disc area. Both AL and SER were strongly correlated with ICP, DCP and CC VD in all regions (all P < 0.01). Larger SSI was correlated with a lower VD in the SCP and ICP, and a higher VD in DCP and CC (all P < 0.01). Conclusion: VD values provide large scale normative data on macular, disc and peripapillary vascular parameters in a large sample of healthy myopic children with OCTA measured in the four different retinal plexuses and regions. The VD in different regions had various influencing factors; mainly a close correlation with AL and SSI.